2017
DOI: 10.11114/afa.v3i1.2196
|View full text |Cite
|
Sign up to set email alerts
|

Firm Characteristics and Compliance with International Financial Reporting Standards (IFRS) by Listed Financial Services Companies in Nigeria

Abstract: This study investigated the level of compliance with International Financial Reporting Standards (IFRS) by listed financial services companies in Nigeria, and the effect firm characteristics have on the level of compliance. The study also examined whether compliance with IFRS significantly differs between listed Deposit Money Banks (DMB) and Insurance Companies (INC) in Nigeria. Secondary data used for the study were extracted from the annual report and accounts of the sampled firms and analyzed using the mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Also, the results are consistent with mainstream of literature on this regard. As many studies reported similar association between company size and level of compliance of IFRSs MDR (Juhmani, 2012;Kumar & Saini, 2016;Samaha & Stapleton, 2009;Sarea & Abdulla, 2015;Tsegba et al, 2017). So, this study confirmed the prior studies in compliance research.…”
Section: Testing the First Hypothesis: Company Size And Mpdrsupporting
confidence: 89%
See 4 more Smart Citations
“…Also, the results are consistent with mainstream of literature on this regard. As many studies reported similar association between company size and level of compliance of IFRSs MDR (Juhmani, 2012;Kumar & Saini, 2016;Samaha & Stapleton, 2009;Sarea & Abdulla, 2015;Tsegba et al, 2017). So, this study confirmed the prior studies in compliance research.…”
Section: Testing the First Hypothesis: Company Size And Mpdrsupporting
confidence: 89%
“…In the developing countries, Tsegba et al (2017) studied the compliance level with IFRS and its impact of the company characteristics as applied to financial companies listed in Nigeria stock market. The results showed that in average the level of compliance around 86% and profitability has positive significant association at 10% while the size of company and the auditor size are positively associated but not significant.…”
Section: Scientific Journal For Financial and Commercial Studies And mentioning
confidence: 99%
See 3 more Smart Citations